Impact of Mindfulness-Based Cognitive Therapy on Depression, Anger and Emotion Regulation of Veterans’ Spouses - S.A. Mehri Nejad (طب جانباز, 2016)
Aims: Having spent many years in mutual life with the vetrans with physical and mental disorders, the spouses of the veterans are facing with mental problems. Therefore, it is necessary to find a way to help the spouses, to improve their mental situation. The aim of this study was to investigate the effectiveness of mindfulness-based cognitive therapy on the veterans’ spouses with depression, anger, and emotion regulation difficulties.